2011
DOI: 10.1001/archophthalmol.2011.270
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Lymphoma of the Lacrimal Gland

Abstract: To characterize the clinicopathologic features of lacrimal gland lymphoma. Methods: All cases of lacrimal gland lymphoma from January 1, 1975, through December 31, 2009, were retrieved from The Danish Registry of Pathology. Histologic specimens were reevaluated using a panel of monoclonal antibodies. Clinical files from all patients with confirmed lymphoma were collected. Results: Twenty-seven patients with lacrimal gland lymphoma were identified. Eight of the patients were men and 19 were women; the median (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
4
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 24 publications
6
39
4
4
Order By: Relevance
“…Of these, 321 patients had primary carcinomas or sarcomas of the lacrimal gland and composed the cohort used in the analysis; the remaining 433 patients had lymphomas and were excluded from the remainder of the data analysis. 19 Of our selected cohort, 55.5% were males and 74.8% were white ( Table 1). The mean age at diagnosis was 57.7 years.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 321 patients had primary carcinomas or sarcomas of the lacrimal gland and composed the cohort used in the analysis; the remaining 433 patients had lymphomas and were excluded from the remainder of the data analysis. 19 Of our selected cohort, 55.5% were males and 74.8% were white ( Table 1). The mean age at diagnosis was 57.7 years.…”
Section: Resultsmentioning
confidence: 99%
“…= B-cell lymphoma, unclassified; CEOP = cyclophosphamide, epirubicin, vincristine and prednisone; CHOP = cyclophosphamide, hydroxydaurubicin, vincristine and prednisone; CLL ⁄ SLL = chronic lymphocytic leukaemia ⁄ small lymphatic lymphoma; DLBCL = diffuse large B-cell lymphoma; EMZL = extranodal marginal zone lymphoma; FL = follicular lymphoma; LDH = lactate dehydrogenase; LG = lacrimal gland; MCL = mantle cell lymphoma; TNM = Tumour, Node, Metastasis. (Rasmussen et al 2011). a full clinical evaluation with up-todate imaging modalities, as defined earlier, was not possible for some of the patients. In these cases, the determination of whether they had primary or secondary lymphoma may be associated with some uncertainty.…”
Section: Clinical Datamentioning
confidence: 99%
“…Its incidence increases with age. [4513] Usually, the MALT subtype of NHL affects other mucosal or epithelial tissues, such as the stomach, salivary gland, and thryroid gland and has an indolent course. The MALT lymphoma of the ocular adnexa usually affects women.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary LGL by definition represents more diffuse and widespread disease and therefore may have a worse prognosis. [4514] The MALT lymphoma is frequently associated with genetic translocations t(11;18(q21;q21),[15] t(14:18)(q32:q31),[16] and trisomy 3. Some of the literature demonstrates an association with Chlamydia psittaci infection, although a study from south Florida has not found a great incidence of C. psittaci infection in their patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation